The Artists in Pandemic, Pandemic in Arts: Artistic Responses to the Ripples of Covid-19 in Nigeria - Adenle, John Oyewole; Akande, Abiodun (NIU Journal of Humanities; Vol 5 No 3 (2020): KIU Journal of Humanities, Vol. 5 No. 3, September 2020, 2020)
The battle between the human race and the coronavirus started as an epidemic in Wuhan China, in 2019 by end of January 2020, there had been reports that almost 10,000 cases of coronavirus and more than 200 people had died. Sooner it was declared pandemic, having spread to many countries and eventually all over the world. Dealing with the unforeseen challenges caused by the COVID-19 and related impacts on health, economies, and even national security in the world became a joint responsibility of international governments. Our ways of life became altered through policies aimed to serve as preventive measures. Varying responses ranging from government proactive interventions and individuals augmenting government gestures by following guidelines of staying safe, this paper discusses the import of visual art in demystifying, recognizing, appreciating and visually comprehending how deadly coronavirus is. A total of 32 respondents that form the sampled population, it traces the diverse involvement of artists, industrial arts and artisans in Nigeria that were gainfully engage in producing face masks and safety kits to augment government efforts. It concludes by considering the responses of people on the patronage of locally produced masks for preventing the spread of Covid 19. Keywords: Coronavirus, Pandemic, face mask, responses, lockdown, visual arts